(untitled) (Hoboken, N.J., 2005)
The single greatest reservoir of usable water for man lies underground. Its location, management, protection and remediation have been a central focus of hydrology for much of the past century. Experts throughout the world have covered this subject, in unimagined detail. Ground water remains unseen but no longer unknown, and now amazingly well defined in every aspect of quality and quantity, development, protection and remediation.
Keywords: Water,Water quality,Water resources development; Supply